Isak Dinesen and narrativity : reassessments for the 1990s - Woods, Gurli A. (Gurli Aagaard), 1942- (Papers (Centre TADAC) ;, 1994)
Responding to recent Dinesen scholarship and public exposure in such films as Out of Africa and Babette's Feast, these fourteen original essays discuss and reveal the aesthetic subtlety and philosophical complexity of Dinesen's art.